Coreference preferences for personal pronouns in German - Bouma, Gerlof; Hopp, Holger (ZAS Papers in Linguistics, 2007)
This paper presents psycholinguistic evidence on the factors governing the resolution of German personal pronouns. To determine the relative influence of linear order versus grammatical function of potential antecedents, two interpretation-preference tasks were designed. Their specific aim was to disentangle salience factors conflated in previous research on pronoun interpretation, such as linear or-der, first mention and topicalization. Experiment 1 tested pronoun resolution to non-sentence-initial position (scrambling) and Experiment 2 tested pronoun resolution to sentence-initial position (topicalization). The results across different verb types and across different syntactic contexts in Experiments 1 and 2 show that grammatical function, yet neither linear order, first mention nor topicalization predicts pronoun resolution in German.